Does Fellowship Matter? A Comparison of Overall Survival and Lymph Node Sampling in Colon Cancer Resections amongst Colorectal Fellowship Trained Surgeons vs. Non-Colorectal Specialty Trained Surgeons - Maranda K. Pahlkotter; John Snyder; Jesse Gygi; William T. Sause; H. Tae Kim (World Journal of Colorectal Surgery)
Background: Approximately 1 in 23 people will be diagnosed with colorectal cancer, resulting in nearly 50,000 cancer related deaths per year in the United States. An effective surgical resection plays an integral role in the success or failure of these patients' oncologic treatment. Objective: This study was designed to focus on lymph node sampling and survival of patients undergoing resections for colon cancer to determine if additional training leads to better outcomes. Design: This is a retrospective review from 2006–2017. Patients who presented through the emergency room were considered elective if their surgery was performed >72 hours after admission. One-hundred and thirty-five surgeons were included, and 13 were colorectal trained. We excluded patients with metachronous or synchronous tumors. Analysis was performed using the Wilcoxon rank sum test. Settings: Twenty-three hospitals within a single healthcare system. Patients: Final analysis included patients undergoing a primary, elective resection for colon cancer. Sample Size: We focused at 2335 patients. Main Outcome Measure: Survival after resection and number of lymph nodes sampled. Results: Among the patients, 2657 met the inclusion criteria, with only 322 resections being considered nonelective. In the elective population of 2335 patients, 536 underwent resection by a colorectal specialty trained surgeon. The survival probability was greater for patients who underwent resection by colorectal surgeons than those for patients who underwent resection by non-colorectal surgeons (p = 9e-05). Lymph node sampling in elective resections by colorectal surgeons was significantly higher (p = < 2e-16), with the mean being 23.8 vs 19.1, respectively. Conclusion: Colorectal trained surgeons have significantly better outcomes than non-specialty trained surgeons considering the overall survival rates and number of lymph nodes sampled for elective resections. Limitations: There was insufficient evidence to conclude that any difference existed in the outcomes when considering the non-elective patient population given the low numbers of these resections being performed by colorectal surgeons. Conflict of Interest: The authors have no conflict of interest to declare.